2018
DOI: 10.1101/271304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Yeast heterochromatin regulators Sir2 and Sir3 act directly at euchromatic DNA replication origins

Abstract: 25Most active DNA replication origins are found within euchromatin, while origins within 26 heterochromatin are often inactive or inhibited. In yeast, origin activity within 27 heterochromatin is negatively controlled by the histone H4K16 deacetylase, Sir2, and at 28 some heterochromatic loci also by the nucleosome binding protein, Sir3. The prevailing 29 view has been that direct functions of Sir2 and Sir3 are confined to heterochromatin. 30However, growth defects in yeast mutants compromised for loading the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…More speci cally, it was recently observed that RSV reduced the H4K16ac mark [20]. In addition, in yeast, Sir2, a target of RSV, negatively controlled the activation of DNA replication origins within heterochromatin and euchromatin by de-acetylating H4K16 [21]. Our results suggest that RSV could be affecting T. gondii transcription and/or replication trough H3 and H4K16 deacetylation.…”
Section: Resultssupporting
confidence: 51%
“…More speci cally, it was recently observed that RSV reduced the H4K16ac mark [20]. In addition, in yeast, Sir2, a target of RSV, negatively controlled the activation of DNA replication origins within heterochromatin and euchromatin by de-acetylating H4K16 [21]. Our results suggest that RSV could be affecting T. gondii transcription and/or replication trough H3 and H4K16 deacetylation.…”
Section: Resultssupporting
confidence: 51%
“…We identified 14 suppressors ( Supplementary Fig. 6a, right panel), of which one affects SIR3 binding (H4-T80A) 37 and another likely affects H3 levels through degradation (H3-Y99A) 28 .…”
Section: Subtelomere Expression Mediates Glucose Starvation Tolerancementioning
confidence: 99%
“…Sir3 localization to euchromatin is not unprecedented. ChIP-seq experiments have detected Sir3 at highly transcribed genes and euchromatic replication origins (12,27,28). While some of the Sir3 signal at highly transcribed genes may be attributed to a ChIP artefact (29), our Nanopore-MetID results suggest that a good number of these genes represent bona fide Sir3 targets.…”
Section: Discussionmentioning
confidence: 68%